VALIDITAS DAN RELIABILTAS ANGKET PROKRASTINASI AKADEMIK - Muhamad Bayu Nuryana; Siti Fatimah; Wiwin Yuliani (IKIP Siliwangi, 2022)
Academic procrastination is a tendency to end a task or work until the end of a predetermined time limit. Academic procrastination results in several unfavorable impacts for the perpetrators, such as being left behind in learning. This study uses research and development methods. This study focuses on presenting the results of validity and reliability of the academic procrastination questionnaire. The results of the validity test of 35 statements given to 85 grade 9 junior high school students showed that there were 32 valid statements with a validity test value of 0.911 where the number was included in the very high category. With this very high category, the questionnaire can be used to collect information about academic procrastination anywhere and anytime. Keywords: Academic Procrastination, Validity, Reliability